Extracting respiratory data from pulse oximeter plethysmogram traces in newborn infants. Issue 4 (17th November 2008) - Wertheim, D; Olden, C; Savage, E; Seddon, P
Abstract : To investigate whether valid respiratory data can be extracted from the pulse oximeter plethysmographic (pleth) trace in healthy newborn infants, pleth data were collected from the foot, and respiratory airflow was simultaneously measured using a facemask. The pleth waveform was analysed using fast Fourier transform (FFT), low-pass filtering (LPF), and by plotting the peak-to-peak amplitude variation (PtP). Using FFT in 14 term infants, the median (range) respiratory rate from the pleth signal was 43 (30–65) breaths/min, and from the flow signal it was 44 (30–67) breaths/min (median difference 0.01 breaths/min, p>0.05). Both LPF and PtP analysis yielded waveforms with a frequency similar to the respiratory rate. Respiratory information, including respiratory rate and a respiratory-like waveform, can reliably be extracted from the pleth trace of a standard pulse oximeter in newborn infants. Such analysis may be clinically useful for non-invasive assessment of respiratory problems in infants and young children.